PENGARUH PENGAWASAN PIMPINAN DAN KEBIJAKAN WORK FROM HOME TERHADAP KINERJA PEGAWAI PADA MASA PANDEMI COVID-19 DI BALAI PENGEMBANGAN KOMPETENSI PUPR WILAYAH V YOGYAKARTA - ARY SUBIYANTORO; Wahyudiyono Wahyudiyono; Himawan Agung Nugroho; Sri Wahyuning; Wini Angraeni (Sekolah Tinggi Ilmu Ekonomi DR KH EZ Mutaqien, 2022)
The purpose of this paper is to determine the effects of supervisory leadership and work from home policies on employee performance during the COVID-19 pandemic at the Regional V Public Works and Housing Competency Development Center Yogyakarta. This writing uses quantitative method. The population used is the staff of the Regional Public Works and Housing Competency Development Center V Yogyakarta. The sampling technique used is Non Probability Sampling. The number of samples is 32. Based on the results of the discussion, it is found that the T observed for leadership supervision is 2.546 > T table 2.048 and the work from home policy of T observed is 3.347 > T table 2.048. This has a partial effect on employee performance. The variable of leadership supervision and work from home policy have a simultaneous effect on employee performance based on the amount of F Test 16,852 > F table 3,33. The contribution of R2 has a strong relationship between leadership supervision and work from home policies in influencing employee performance, which is 0.538 or 53.8%.